(untitled) (World Economics and Finance Bulletin, 2024)
The infrastructure gap in developing countries is caused by insufficient public funding as well as an ineffective mechanism for directing private funding towards the intended goals. To close the infrastructural deficit, the public-private partnership (PPP) method was developed. However, due to the lengthy contracts and wide range of stakeholders involved, PPP projects are frequently vulnerable to financial difficulty or, worse, termination. Indeed Uzbekistan, like many other countries, has substantial infrastructure needs in order to sustain economic growth and raise the standard of living for its people. Uzbekistan may contemplate executing various infrastructure projects, such as those related to transportation, energy, water management, telecommunications, and other areas.